Profit-led in effect or in mere appearance? Estimating the Irish demand regime given the influence of multinational enterprises - Ryan Woodgate (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
In the Republic of Ireland, the activities of MNEs drive real demand on one level and severely distort conventional national accounts statistics on another. This poses a problem for the valid estimation of the Irish demand regime since key variables such as the wage share of GDP are skewed and strongly correlated with omitted variables that determine some components of demand. This paper summarises the real and distortionary effects of MNEs in Ireland, and then adjusts and controls for these effects as much as possible in an econometric estimation of the underlying Irish demand regime. Both ordinary least squares and three stage least squares estimators are used, the latter as an attempt to deal with the issue of simultaneity bias that confronts all empirical attempts at demand regime estimation. The main results of this paper are twofold. Firstly, Ireland is found to be wage-led in the specifications that adjust and control for the influence of MNEs. Second, the average effective corporate tax rate (AECTR) on foreign affiliates in Ireland is found to be statistically significant in explaining investment. This, alongside indicative foreign affiliate statistics, supports the view that Ireland may be "tax competition-led", in the sense implied by Woodgate (2020), where a lower AECTR has a net positive effect on aggregate demand in Ireland (though at the expense of other nations). The implications of these findings for policy are drawn.
Keywords: E11; E12; E25; C22; C36; 330; Distribution; demand regime; Ireland; tax competition; profit shifting